1983
DOI: 10.1016/s0735-1097(83)80100-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of exercise thallium-201 imaging in patients presenting for evaluation of chest pain

Abstract: Accurate prognostic information is important in determining optimal management of patients presenting for evaluation of chest pain. In this study, the ability of exercise thallium-201 myocardial imaging to predict future cardiac events (cardiovascular death or nonfatal myocardial infarction) was correlated with clinical, coronary and left ventricular angiographic and exercise electrocardiographic data in 139 consecutive, nonsurgically managed patients followed-up over a 3 to 5 year period (mean follow-up, 3.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
4

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(63 citation statements)
references
References 20 publications
1
57
1
4
Order By: Relevance
“…The best predictor of cardiac death or non-fatal MI was the number of myocardial segments with transient defects on 201 TI imaging. (8) Although the presence of jeopardized viable myocardium identifi es patients at increased risk for cardiac events, more importantly cardiac risk is directly related to the extent of jeopardized viable myocardium.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…The best predictor of cardiac death or non-fatal MI was the number of myocardial segments with transient defects on 201 TI imaging. (8) Although the presence of jeopardized viable myocardium identifi es patients at increased risk for cardiac events, more importantly cardiac risk is directly related to the extent of jeopardized viable myocardium.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…Many studies demonstrated that the presence and extent of myocardial ischemia was closely related to adverse cardiac events [26][27][28][29][30][31][32][33][34][35][36] . Hachamovitch et al [36] identified 5183 patients who underwent MPI and were followed up for the occurrence of cardiac death or myocardial infarction.…”
Section: Mpimentioning
confidence: 99%
“…4 The prognostic value of the extent of myocardium at risk (as assessed by extent of reversible perfusion defects with Tl-201), and its subsequent relationship with cardiac death was initially described in a study of 100 patients with no known history of myocardial infarction who presented for evaluation of chest pain. 5 Since then, there have been a multitude of studies documenting the ability of abnormal MPS in predicting future cardiac deaths, nonfatal myocardial infarction and revascularization. 6,7 Equally, a negative/ normal MPS was shown to be associated with a good prognostic outcome.…”
Section: Diagnostic and Prognostic Value Of Myocardial Perfusion Scinmentioning
confidence: 99%